S72 Paediatric pneumococcal empyema serotypes have not changed following introduction of the 13 valent pneumococcal vaccine. (14th November 2013) - Thomas, MF; Sheppard, C; Guiver, M; Simmister, C; Elemraid, MA; Clark, JE; Rushton, SP; Paton, JY; Spencer, DA
Abstract : Introduction: Pneumococcal infection is the leading cause of paediatric empyema in the UK. Prior to the change in the UK routine vaccination schedule from the seven valent conjugate pneumococcal vaccine (PCV-7) to the thirteen valent vaccine (PCV-13) in April 2010 four serotypes /serogroups–1, 3, 7A/F and 19A accounted for 75% of culture negative pneumococcal empyema in UK children. Antigen for these four serotypes is not present in PCV-7 but is present in PCV-13. We examined the impact of PCV-13 on the incidence of disease due to serotypes 1, 3, 7A/F and 19A using national surveillance data from the UK-ESPE study. Methods: Pleural fluid samples were forwarded from admitting hospitals. Those that were pneumococcal PCR positive underwent non-culture serotyping using a multiplex antigen detection assay capable of detecting 14 serotypes/groups (1, 3, 4, 5, 6A/C, 6B, 7F/A, 8, 9V, 14, 18, 19A, 19F and 23F). Two time periods were analysed April 2008–April 2010 (PCV-7 era) and April 2010–April 2012 (PCV-13 era). Incidence rate ratios (IRR) were calculated for individual serotypes. Age distributions were compared by density plotting. Results: 380 samples (median age 3.8 years) were tested in the two time periods (191 PCV-7 era, 189 PCV-13 era). No reduction in the incidence of empyema caused by the four main serotypes/groups (IRR: Serotype 1–0.79 95% CI (0.57–1.11), 3–0.91 (0.60–1.37), 7A/F–1.59 (0.85–3.04), 19A–2.42 (1.61–5.40)) was seen and 19A increased significantly. The age distribution of each serotype did not change between the two time periods. Discussion: The introduction of PCV-13 has not yet been associated with any reduction in the incidence of vaccine serotype pneumococcal empyema in children in the UK, in contrast to the changes following the introduction of PCV-7. The factors contributing to this remain unclear but may include a predominantly PCV-7 vaccinated cohort, insufficient herd immunity, inadequate immunological response to vaccine antigen or on-going secular trends. Continuing surveillance is essential and will provide important data on future trends to better understand these complex processes.